Evaluation of the Effects of Topical Vitamin D on Osseointegration of Titanium Implants: An Experimental Study - Bozoglan, Alihan; Dündar, Serkan (My University, 2021)
Background: The aim of this study was to evaluate the effects of topical vitamin D to on osseointegration when applied to the surface of titanium implants.Material and Metods: Twenty male Spraque-Dawley rats were used in this study in a 4-week experimental period. 4 rats died during the experiments. The rats were divided into 2 groups: a test group and control group. Sixteen sandblasted and acid-etched implants were integrated surgically in the metaphyseal part of rat femurs after patella dissection. Prior to integration, the implants, which were 3.2 mm in diameter and 8 mm in length, were submerged in a 10% vitamin D solution in the test group. No treatment was applied in the control group. After the 4-week experimental period, the rats were sacrificed, and the implants were removed with surrounding bone tissue. Specimens were fixed for 7 days in a 10% formaldehyde solution. Bone implant contact (BIC) ratios were determined after using non-decalcified histological methods.Results: In the experiment, 2 samples were removed because they were not suitable. No statistically significant differences were found for BIC ratios between the test (n = 7) and control group (n = 7) implants (P> 0.05). Conclusion: It was concluded, within the limitations of this animal study, that topical vitamin D application on implant surfaces does not affect BIC ratios.
Keywords: Topical vitamin-d; rat femoral bone; bone implant contact; osseointegration